Gypsies in Siberia (end of the 18th – 20th century) - Shaidurov, Vladimir N.; Sapronova, Natalia A.; Goncharov, Yurii M.; Novogrodski, Tadeush A. (Journal of the Belarusian State University. History, 2022)
The history of the Roma in Russia is a poorly studied topic. The article discusses the main stages in the formation and development of the Gypsy community in Siberia during the late 18th – 20th century. The authors came to the conclusion that the main source for the emergence and growth of the number of Roma in the region was migration, in which Belarusian Roma played an important role. On the basis of various sources, a description is given of the measures taken by the authorities in relation to the Roma population, aimed at its homogenisation and integration into the economic and socio-cultural processes in Siberia. However, all campaigns to combat Gypsy vagrancy in the 19th and 20th centuries did not lead to its complete eradication. The repressive steps both in the second quarter of the 19th century and in the 1930s did not help to solve the problem either. Only a part of the Gypsies switched from a traditional to a semi-sedentary way of life. Archival materials from central and regional archives. Most of the documents are introduced into scientific circulation for the first time.
Keywords: Gypsies; Siberia; state policy; vagrancy